Kingship and Maritime Power in 10th‐Century England. (1st September 2020) - Firth, Matthew; Sebo, Erin
Abstract: Ships and seafaring were intrinsic to early English cultures, identifiable in the origin story of the adventus Saxonum, in the material cultures of 6th‐ to 10th‐century England, and in later portrayals of good kingship. However, effective control of the sea only became critical to Anglo‐Saxon kings in the 10th century, serving to legitimate their authority and demonstrate both power and prestige. Using a combination of historical texts and archaeological evidence, this article examines the intersection of kingship and sea‐power in 10th‐century England, both as practical necessity and cultural symbol of legitimate kingly authority.